A generic preventive maintenance framework of industrial boiler corrosion - Alazemi, Nader S TH O S (Kulliyyah of Engineering, International Islamic University Malaysia, 2022)
In the oil and gas industries, numerous factors affect boiler performance and one of the more critical ones is corrosion. In addressing this particular problem, a number of related studies have been conducted, such as statistical analysis, analysis of variance, and optimisation techniques. In this study, the corrosion problems affecting the oil and gas industries in Kuwait were looked into, since it is one of the major global producers and exporters of crude oil, used as fuels for the source of energy, during the steam generation in the industrial boilers. However, the presence of various chemical substances on the boiler surface creates problems of corrosion, attributed to losses worth billions of dollars, every year, in various organisations. Much effort has been taken by many researchers and practitioners, in finding out efficient solutions. Every industry has different responsibilities and structures, and applying one solution for every industry is complex. Therefore, this study aimed to fill this research gap and build up a new prevention system that shows the generalised results. In this study, a systematic literature review, based on preliminary studies in corrosion, was conducted, to examine all the contributing factors, sources of corrosion, and the present corrosion prevention systems. After determining all the contributing factors and identifying shortcomings in previous studies, a five-point Likert scale boiler corrosion survey was conducted, along with an empirical validation and a convenience sampling, in the oil and gas industries, in Kuwait. Statistical Package for the Social Sciences (SPSS 2.0) was used to find the skewness and the set of main factors for the problem. Using the design science approach, a new corrosion prevention management framework was successfully developed, which could be applied to each industry. This new corrosion prevention management framework represents generalised results for all the present corrosion problems, and is to be used to validate the relevance and rigours of any relevant research, using the Hevner’s seven-step approach, to provide a viable artefact for various research problems. An analysis of variance was used to determine the data optimisation, with predictable results. This shows the numerous factors that affect the corrosion performance of boilers in Kuwait's specific gas and oil industries. This framework is efficient, in terms of both managerial and technical perspectives, as proven by its cost-based analysis.